PENGEMBANGAN MODUL ELEKTRONIK (E-MODUL) IPAS BERBASIS MODEL PROJECT BASED LEARNING (PJBL) PADA KELAS IV DI SDN 06 SITIUNG KABUPATEN DHARMASRAYA - Anggrayni, M.; Susilawati, Wiwik Okta; Batuzzulfa, Ady; Putri, Dhara Atika; Kharisna, Feby (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
The aim of this research is to develop teaching materials in the form of IPAS Electronic Modules (E-Modules) Based on the Project Based Learning (PJBL) Model, in order to add interesting teaching materials and improve student learning outcomes so as to achieve learning goals. This type of research and development uses the Research & Development (R & D) type of research. The model used is the development of ADDIE which includes the analysis stage (Analyze), namely needs analysis, material analysis, analysis of teaching materials used in schools and analysis of student characteristics. The design stage is the E-Module design stage and the research instrument design stage. The development stage is the development stage where validity tests are carried out by experts. The implementation stage is the practicality trial stage, and the evaluation stage is the effectiveness evaluation stage carried out at SDN 06 Sitiung. The results of the IPAS E-Module validation research in the validation test by 5 experts obtained an average score of 86.6% in the very valid category. The practicality test assessed from the teacher response questionnaire got an average score of 95% in the very practical category and students got an average score of 91% in the very practical category. Meanwhile, the results of the IPAS E-Module effectiveness test were obtained from the results of the effectiveness test in the form of test questions filled in by students and obtained a percentage of 85.7% in the very effective category.